An optimized pressure vessel obtained by metal additive manufacturing: Preliminary results. (August 2021) - Abdalla, Hassan Mohamed Abdelalim; Casagrande, Daniele; De Bona, Francesco; De Monte, Thomas; Sortino, Marco; Totis, Giovanni
Abstract: The feasibility of a pressure vessel shape optimization is here investigated. An analytical procedure based on calculus of variations is used for the shape optimization of a naturally closed pressure vessel aiming at either minimizing the mass or maximizing the volume under structural integrity constraints. The obtained shapes are ellipsoids with variable thickness along the meridian. Such geometry is suitable to be manufactured by means of advanced processes such as additive techniques. A metallic technology demonstrator was successfully produced by using a 3D printing facility. Optical scanner measurements proved that the process was able to fulfil the required geometry with technically acceptable manufacturing tolerances. Finally, a Finite Element analysis was performed on the measured geometry, confirming that the stress distribution fits well with the theoretical expectations and fully satisfies the optimization constraints. Highlights: An analytical procedure based on calculus of variations is used for the shape optimization of a pressure vessel. A technology demonstrator was successfully produced by means of metal additive manufacturing. Optical laser measurement showed that the required geometrical tolerances were achieved. The stress distribution obtained with a Finite Element analysis fits well with the optimization constraints.